2022
DOI: 10.1007/s00213-021-06052-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in affective states and association with voluntary ethanol intake in Sprague–Dawley rats

Abstract: Alcohol use disorders (AUDs) are a major problem across the United States. While AUD remains a complex human condition, it is difficult to isolate the directionality of anxiety and ethanol (EtOH) drinking from outside influences. The present study sought to investigate the relationship between affective states and EtOH intake using male and female Sprague Dawley rats. Using complementary tests of anxiety-and depressive-like behavior, we found sex-and test-specific differences in basal affective behavior such t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Other studies show that female mice and rats acquire ethanol self-administration faster (Melón et al 2013 ; Moore and Lynch 2015 ), show less withdrawal symptoms (Varlinskaya and Spear 2004 ), and have a lower response to pharmacological treatments for AUD (Moore and Lynch 2015 ) compared to males. However, studies have reported greater ethanol consumption in adolescent males (Vetter-O'Hagen et al 2009 ) or have found no sex differences in either adolescent (Lancaster et al 1996 ) or adult (Quadir et al 2022 ) rats. However, Quadir et al ( 2022 ) did find sex-dependent interactions of affective states with ethanol intake and how the two may influence each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies show that female mice and rats acquire ethanol self-administration faster (Melón et al 2013 ; Moore and Lynch 2015 ), show less withdrawal symptoms (Varlinskaya and Spear 2004 ), and have a lower response to pharmacological treatments for AUD (Moore and Lynch 2015 ) compared to males. However, studies have reported greater ethanol consumption in adolescent males (Vetter-O'Hagen et al 2009 ) or have found no sex differences in either adolescent (Lancaster et al 1996 ) or adult (Quadir et al 2022 ) rats. However, Quadir et al ( 2022 ) did find sex-dependent interactions of affective states with ethanol intake and how the two may influence each other.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have reported greater ethanol consumption in adolescent males (Vetter-O'Hagen et al 2009 ) or have found no sex differences in either adolescent (Lancaster et al 1996 ) or adult (Quadir et al 2022 ) rats. However, Quadir et al ( 2022 ) did find sex-dependent interactions of affective states with ethanol intake and how the two may influence each other. The enhanced rewarding effects in females are also apparent in conditioned place preference studies, where adult females show a clear preference for ethanol, while males do not (Torres et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, affective tests are rarely repeated in the same subjects; thus, there are limited findings regarding the effects of time and re-testing on behavior. In one study, researchers found that male rats, but not female rats, spent significantly less time grooming on the second splash test 70 . While the current findings indicate decreased motivation regardless of sex, strain differences may account for this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Splash testing was conducted in the modified home cage based on procedures from Quadir and colleagues 37 . After 2 min acclimation, mice were exposed to a spray of sucrose (10% w/v; in DI water), delivered from an atomizer (100 uL) to the dorsal coat.…”
Section: Methodsmentioning
confidence: 99%